Police reform in public housing contexts: Body-worn cameras, surveillance, and harm reduction in New York City Housing Authority developments - Braga, Anthony Allan (Criminology & public policy, 2024)
Research summary The concern of crime in New York City public housing complexes motivated heightened police patrol of buildings and the enforcement of trespass laws. The 2013 federal court settlement of Davis et al. v. City of New York et al. mandated that the New York City Police Department (NYPD) implement a series of reforms, including the deployment of body-worn cameras (BWCs) on officers, to address unconstitutional use of criminal trespass enforcement and stop and frisk practices in public housing developments. This study employed a stepped wedge quasi-experimental design that involved the sequential crossover of public housing service area clusters from control to BWC implementation until all NYPD housing bureau officers were equipped with BWCs. Panel regression models at the individual officer and service area levels were used to estimate BWC program impacts on outcomes between 2015 and 2019. Logistic regression models were used to estimate the impact of the BWCs on the lawfulness of officer stop reports that were randomly selected for audit between 2017 and 2019. Results show that BWC deployment in public housing reduced excessive enforcement, citizen complaints, and use of force by NYPD housing officers. Findings further suggest that BWCs can help reduce constitutionally problematic stops and frisks of citizens. Policy implications Problematic police activities in public housing contexts can be reformed using BWCs. When coupled with routine supervisory review of video footage, the deployment of BWCs on public housing officers can improve compliance with department directives to reduce enforcement actions and increase documentation of citizen stops.